The future of food, land and water systems under emerging digital technologies in the Global South workshop - Veeger, Marieke; Jimenez Rodas, Daniel; Garcia Andarcia, Mariangel (2025)
A brief concept note describing the purpose, methodology, and expected outcomes of a participatory future scenarios workshop focused on digital technologies and their long-term implications for food, land, and water systems.